Public health risks threatening health of people participating in mass gatherings: A qualitative study - Asghar Tavan; Abbasali Dehghani Tafti; Mahmood Nekoie-Moghadam; Mohmmadhasan Ehrampoush; Mohammad Reza Vafaei Nasab; Hossein Tavangar (Wolters Kluwer Medknow Publications, 2020)
Background: Mass gatherings (MGs) have made many problems for the health system and potentially threaten the health of those participated in these gatherings. MGs account for a range of public health risks including communicable diseases, waterborne diseases, water treatment, and outbreaks. Objectives: The present study aimed to identify public health risks threatening the health of people participating in MGs in Iran. Methods: A qualitative study was designed using a conventional qualitative content analysis approach. Participants were selected using a purposive sampling method among the managers and staff who have experiences in the field of health in MGs in Iran. Subjects were interviewed through individual in-depth interviews after obtaining informed consent. Semi-structured interviews were used to collect the data from December 2018 to February 2019. To analyze the data, the content of recorded interviews was written verbatim. Preliminary data were repeatedly and simultaneously retrieved to give a general understanding of them. Results: The main theme emerged from data analysis on 16 interviews was related to public health risks involving the following categories: food hygiene deficiencies, communicable diseases risks, defects in health supervision, and the risk of environmental contamination. Conclusion: It is of paramount importance to identify the risks threatening the health of people participating in MGs. In the present study, the main public health risks were detected.